2017
DOI: 10.3390/app7121270
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Cyclic Strength for the Asphalt Concrete Considering Damage Accumulation

Abstract: Abstract:The expression is obtained for determination of cyclic tensile strength for asphalt concrete, which considers damage accumulation and history of loading, using the long-term strength curve for asphalt concrete obtained according to the test results of more than 110 samples to failure at stresses from 0.05 to 0.31 MPa and by introduction of damage kernel in this paper. Cyclic strength depends on the stress, parameters of long-term strength, frequency of loading, durations of loading and relax periods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Comparison of the calculation results performed under the obtained expression, and experimental tests showed that the obtained expression describes satisfactorily the cyclic tensile strength of the asphalt concrete. It was concluded that the obtained expression for determination of the cyclic tensile strength for the asphalt concrete can be used for the prediction of fatigue strength of the asphalt concrete pavement, Iskakbayev et al, (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the calculation results performed under the obtained expression, and experimental tests showed that the obtained expression describes satisfactorily the cyclic tensile strength of the asphalt concrete. It was concluded that the obtained expression for determination of the cyclic tensile strength for the asphalt concrete can be used for the prediction of fatigue strength of the asphalt concrete pavement, Iskakbayev et al, (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Creep and relaxation are important characteristics of hereditary materials. The creep has been studied for an asphalt concrete and other materials in the works [5][6][7][8][9][10][11][12][13]. The present work is devoted to the modeling of the process for relaxation of a number of hereditary materials.…”
Section: Introductionmentioning
confidence: 99%
“…In Kazakhstan complex experimental and theoretical research for deformation and strength of asphalt concretes is carried out [9][10][11][12][13][14][15][16][17][18][19][20]. The current paper is continuation of the above works and it considers the matters of computer modeling for creep procedure of hereditary materials using nonlinear integral equation of Yu…”
Section: Introductionmentioning
confidence: 99%